Comparison of bioactivities and phenolic composition of Choerospondias axillaris peels and fleshes. (20th October 2015) - Li, Qian; Chen, Jun; Li, Ti; Liu, Chengmei; Liu, Wei; Liu, Jiyan
Abstract: BACKGROUND: Choerospondias axillaris is both an edible and medicinal fruit. It has a growing popularity and economic importance due to its nutritive value and medicinal effects, but comprehensive information on the chemical composition and bioactivity of its fruits is still lacking. Therefore the aim of this study was to investigate the antioxidant, antimicrobial and antiproliferative effects and chemical composition of peel polyphenolic (PP) and flesh polyphenolic (FP) extracts from C. axillaris . RESULTS: The phenolics and flavonoids of peel were significantly higher than those of flesh. Ultra‐performance liquid chromatography (UPLC) and ultra‐performance liquid chromatography/electrospray ionization quadrupole time‐of‐flight‐mass spectrometry (UPLC/ESI‐QTOF‐MS 2 ) analysis revealed that (+)‐catechin and oligomeric procyanidins were the most abundant compounds in PP and FP. Both extracts exhibited strong ferric‐reducing antioxidant power, total antioxidant activity and 2, 2‐diphenyl‐1‐picrylhydrazyl radical (DPPH )‐scavenging ability. PP showed a significantly higher antimicrobial effect against tested strains than that of FP, in a dose‐dependent manner. Furthermore, both extracts inhibited the growth of HepG2 and Caco‐2 cells in a dose‐ and time‐dependent manner, with IC50 values of 39.31 and 47.49 µg mL −1 to HepG2 cells and 101.90 and 102.61 µg mL −1 to Caco‐2 cells respectively. CONCLUSION: This is the first detailed report on the chemical composition and bioactivities of C. axillaris fruits. © 2015 Society of Chemical Industry